Job insecurity and job experience on salesperson performance mediated by work engagement - Hani Jayanti; Siti Nur Azizah (Jurnal Mantik, 2026)
Sales performance differs notably among individuals, yet each salesperson plays a crucial role in achieving organizational targets. These differences can be influenced by various factors, including job insecurity and job experience. This study investigates how job insecurity and job experience affect job performance, with work engagement as a mediating factor, focusing on car salespersons in Kebumen Regency. Using a quantitative approach and Partial Least Squares–Structural Equation Modeling (PLS-SEM), data were collected from 62 respondents. The results reveal that job insecurity has no significant impact on work engagement or job performance. In contrast, job experience positively and significantly affects both work engagement and performance. Mediation analysis shows that work engagement significantly mediates the effect of job experience on performance, but not for job insecurity. These findings highlight that while work engagement can amplify the benefits of job experience, it does not counteract the negative effects of job insecurity. Managers are thus advised to enhance work engagement and